PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEBAK KATA DAN KELILING BERKELOMPOK TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DI KELAS VIII SMP NEGERI 2 KOTA JAMBI - Sapitri, Sapitri; Andriani, Lili (Universitas Batanghari Jambi, 2021)
AbstractThis study aims to determine the learning outcomes of students who are taught using a cooperative learning model type Guess the word and group around in social studies subjects in class VIII SMP Negeri 2 Jambi City and a comparison of the cooperative learning model type Guess the Word and Go Around Groups on student learning outcomes in the subject. Social Studies lessons in Class VIII SMP Negeri 2 Jambi City. The type of research conducted is a quasi-experiment. The guessing type cooperative learning model for class VII C (control) and the group traveling type cooperative learning model for class VIII B (experimental). Sampling in this study used purposive sampling technique, so that 38 students of class VIII C were selected as the control class and 32 students of class VIII B as the experimental class. Data collection techniques are carried out by distributing questions to research respondents and documentation. The data analysis technique used the t-test. The results showed that the average value of posttest learning outcomes for class VIII B (experimental class) was 10,063 and the average value for learning outcomes for social studies subjects in the posttest stage in class VIII C was 8.079. Based on these results, the average value of learning outcomes for social studies subjects at the posttest stage in class VIII B is higher than class VIII C. The results of the t-test show a t-count value of 8.480 and a significance value of 0.000 <0.05, so H0 is rejected. and Hadi Accept. Based on these results, the cooperative learning model type Guess the Word and Go Around in Groups has an effect on student learning outcomes in social studies subjects in Class VIII SMP Negeri 2 Jambi City.Keywords: Cooperative Learning Model Type Guess the Word and Mobile Group, Learning Outcomes